Intan School Bus Management System - Ahmad, Nur Fatin Syafiqah; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2024)
The Intan School Bus specializes in providing transportation services for primary school students. This current process relies on a non-computerized system, leading to data loss, payment inefficiencies, and time-consuming processes. The project objectives involve designing a school bus management system using object-oriented approach, developing the system using web-based approach, and testing through system and user acceptance testing. The proposed system implements seven modules which are registration, login, manage profile, manage transportation, manage payment, track school bus, and generate report. The project uses prototyping methodology as the software development life cycle model. After system deployment, users can register for the Intan School Bus Management System, and administrator can manage user data through web browsers. The project completion aims to deliver a web-based system for Intan School Bus Management that facilitates the user registration process and ensures efficient data management for the school bus service.